IDENTIFICATION OF FLOOD PRONE AREAS IN MARIAT DISTRICT, SORONG DISTRICT USING GEOGRAPHIC SYSTEMS (GIS) - Putra, Kurniawan Budi Hartono; Butudoka, Marina Abriani (Casuarina: Jurnal Teknik Lingkungan, 2023)
On June 8 2019, the Mariat River, located in Mariat District, Sorong Regency, West Papua, overflowed due to high intensity and long-lasting rain, resulting in hundreds of residential units and hundreds of hectares of plantation land along the banks of the river being submerged in flood waters as high as 0.5 meters. – 1 meter. One effort that can be made to identify flood-prone areas in Mariat District, Sorong Regency is to conduct a Geographic Information System (GIS) study. This research aims to determine the distribution of flood-prone locations in Mariat District, Sorong Regency and find out how wide the flood inundation area is in each sub-district of Mariat District, Sorong Regency. The results of this research are a map of flood-prone areas in Mariat District, Sorong Regency and a map of the area of ​​flood inundation in each sub-district of Mariat District, Sorong Regency. The research results show that the areas affected by flooding in Mariat District, Sorong Regency are only 3 sub-districts, namely Klamalu sub-district, Klasuluk sub-district and Mariyai sub-district with a percentage of 18% of the total area in the three sub-districts. Meanwhile, the area affected by flooding in Mariat District, Sorong Regency includes three sub-districts, namely Klamalu Sub-district with a flood-affected area of ​​1.0479 km2 or 14% of the total area of ​​the sub-district, Klasuluk sub-district with a flood-affected area of ​​0.7995 km2 or 18% of the total area of ​​the sub-district. , and Mariyai Village flood-affected area of ​​0.6195 km2, 40% of the total area of ​​the Village.